PHYSICOCHEMICAL PROPERTIES OF GINGER, CURCUMA, TURMERIC, AND PANGLAI'S STARCH - KOMALA SARI (NIM : 10508031); Pembimbing : Dr. Zeily Nurachman, RATNA
Rhizomes have been used as main ingredients of food, cosmetic, and essential oil industries in Indonesia. However, so far there are many physical and chemical properties of rhizome starch yet to be unknown. The purpose of this study is to characterize the physicochemical properties of starches isolated from several rhizomes: ginger, curcuma, turmeric and panglai. Physicochemical properties of the starches such as water content, ash content, metal content, protein content, viscosity, calorie value, dextrose equivalent, starch granule morphology were observed. The results showed that iodine tests to four types of starches obtained from various rhizome sources was positively suggesting the starches were true. All starches exhibited moisture content in a range of 11Ã‚Â–14%; ash content 0.2Ã‚Â–0.7%; metal content, such as Fe, Mg, Mn, Ca, and Na 1Ã‚Â–4, 1Ã‚Â–5, 1Ã‚Â–3, 1Ã‚Â–6, and 1Ã‚Â–6 ppm respectively; protein content 0.6Ã‚Â–0.8%; viscosity of 2% starch solution 1Ã‚Â–14 mPa s; calorie value 350Ã‚Â–380 kkal/100 g starch; and dextrose equivalent value of null. Starch granule morphologies of ginger, curcuma, turmeric and panglai were a disc (17.5ÃƒÂ—11.65ÃƒÂ—2.5 μm), elongate disc (41ÃƒÂ—23ÃƒÂ—5 μm), elongate disc (36ÃƒÂ—20ÃƒÂ—6 μm), and disc (42.5ÃƒÂ—30ÃƒÂ—5 μm) respectively. Based on the physicochemical properties, four different rhizomes of ginger, curcuma, turmeric and panglai can be used for an alternative carbohydrate sources, and the starches can be used for staple food to complement existing rice.